Cumulative response of ecosystem carbon and nitrogen stocks to chronic CO2 exposure in a subtropical oak woodland. Issue 3 (30th May 2013) - Hungate, Bruce A.; Dijkstra, Paul; Wu, Zhuoting; Duval, Benjamin D.; Day, Frank P.; Johnson, Dale W.; Megonigal, J. Patrick; Brown, Alisha L. P.; Garland, Jay L.
Summary: Rising atmospheric carbon dioxide (CO2 ) could alter the carbon (C) and nitrogen (N) content of ecosystems, yet the magnitude of these effects are not well known. We examined C and N budgets of a subtropical woodland after 11 yr of exposure to elevated CO2 . We used open‐top chambers to manipulate CO2 during regrowth after fire, and measured C, N and tracer 15 N in ecosystem components throughout the experiment. Elevated CO2 increased plant C and tended to increase plant N but did not significantly increase whole‐system C or N. Elevated CO2 increased soil microbial activity and labile soil C, but more slowly cycling soil C pools tended to decline. Recovery of a long‐term 15 N tracer indicated that CO2 exposure increased N losses and altered N distribution, with no effect on N inputs. Increased plant C accrual was accompanied by higher soil microbial activity and increased C losses from soil, yielding no statistically detectable effect of elevated CO2 on net ecosystem C uptake. These findings challenge the treatment of terrestrial ecosystems responses to elevated CO2 in current biogeochemical models, where the effect of elevated CO2 on ecosystem C balance is described as enhanced photosynthesis and plant growth with decomposition as a first‐order response.